Lo sublime hecho carne: la representación estética de la criatura en Frankenstein. The sublime made flesh: aesthetic representation of the creature in Frankenstein - González Moreno, Beatriz (Estudios Ingleses de la Universidad Complutense, 2003)
Mary Shelley’s appeal to horror and terror as a means of referring to Victor’s monstrous creation was certainly indicative of the nineteenth century’s fascination with the philosopher Edmond Burke and his elaborate aesthetics of the sublime. Bearing that in mind, this article aims at showing the ways in which the creature is a aestheticised both externally and internally, non only by the rest of the characters but also by the monster himself and the aesthetic reader. 1 will then explore the relationship this incarnate sublimity is to maintain with prevailing ethics in society, that is, the Platonic equation between beauty and goodness. In this context, Frankenstein may be analysed as a tale that develops from a moral transgression to an aesthetic one; and, correspondingly, the creature embodies a movement from love inspiring beauty to fear-menacing sublimity.